Testing Effects of Changes in Earing to Dividend Actions of Listed Firm on Vietnamese Stock Exchanges Using the Multinominal Logistic Regression Model - Nguyen, Van Dinh (VNU Journal of Science, 2019)
This paper aims to fill the gap in dividend policy research of listed companies in Vietnam. Effects of changes in earning to changes in dividend actions of selected listed firms are tested in order to figure out their ralationships. The multinational logistic regression model is employed with the data from 2008 to 2016. The study has estimated odds and odds ratios of four dividend change cases in response to each of three cases of earnings changes. The results show that the dividend action higher of odds that increase dividend, lower than odds that decrease dividend when earnings decrease, and lower than odds that firm move to zero dividend when 27% when earnings decrease. The results are supportive of the hypothesis that dividend actions are strongly affected by firms' earning and past dividend actions. The rasearch results are meaningful to dividend income investors in formulating their investment strategies and for management of firms in designing firms' dividend policies.